Predicting Residual Life of Toro-40D Units Using the Oil Spectral Analysis Method - Bakytzhan Kyrgyzbay; Mergen Zhumanov; Yerbol Kaliyev; Nurbol Kamzanov; Nursat Baikenzhe; Rustem Kozbagarov (Communications, 2025)
At the underground mines of Kazakhmys Corporation, where different types of highly productive self-propelled equipment with different types of pneumatic wheel drive are operated, there are significant downtime of technological equipment. As practice has shown, application of repair system with use of old methods and means, at operation of underground self-propelled equipment appeared to be ineffective. One of the main reasons of low efficiency of self-propelled machines operation is the absence of the system of continuous monitoring of technical condition of each machine and its aggregates with application of methods and means of diagnostics. To avoid failure, it is necessary to establish the predicted and residual resource at a certain operating time of the machine according to the diagnostics data. This paper outlines the results of research on predicting the residual life of machine units used in the conditions of the mine corporation "Kazakhmys".